PERDEBATAN SEPUTAR AHL AL-KITAB - Sya’roni, Sam’ani (IAIN Pekalongan, 2010)
Ahl al-Kitab is a very popular term but it is still not clear to those who are meant by the term and it is always debated by Islamic scholars, both classical and contemporary. Is the term identical with Jews and Christian only or it also include other believers, like Zoroastrian, Shabi’in, and even Hindis or Buddhist? Discourse of the coverage of the term is certainly very interesting to discuss because it can give wide law implication in social life like marriage with them and their slaughtered animal.